Penggunaan Media Audio Visual untuk Meningkatkan Aktivitas dan Kemampuan Menyimak Teori Pembelajaran Bahasa Indonesia Siswa Kelas V SD - Andari; Sudigdo, Anang; Santosa, Wijaya Heru (Indonesian Journal of Learning and Educational Studies, 2023)
This research aims to explore the effectiveness of using audio-visual media in enhancing the activity and listening comprehension skills in the Indonesian language learning theory among fifth-grade elementary school students. This study adopts the classroom action research approach. The participants consist of 17 fifth-grade students from a selected elementary school chosen purposively. Each cycle comprises four stages: (1) planning, involving the development of a lesson plan focusing on the utilization of audio-visual media; (2) implementation, encompassing the execution of the lesson plan and the incorporation of audio-visual media in the learning process; (3) observation, which includes monitoring student activities and their responses to the audio-visual media; and (4) reflection, involving the evaluation and adjustment of teaching strategies for the subsequent cycle. The average listening comprehension score for fictional stories in Cycle II was 78.38, showing an increase of 15.74 compared to Cycle I, which was 62.64. The number of students meeting the Minimum Mastery Criteria (KKM) also increased. In the first meeting of Cycle I, only 6 out of 17 students, or 35.29%, met the KKM. Subsequently, in the second meeting of Cycle I, there was an increase of 16 students, or 48.23%, meeting the KKM. In the second meeting of Cycle II, there was an increase of 15 students, or 88.23%, meeting the KKM.